1999
DOI: 10.1016/s0165-2370(99)00016-9
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of auto shredder residue: experiments with a laboratory screw kiln reactor

Abstract: The pyrolysis of automobile shredder residue (ASR) has been studied using a laboratory scale screw kiln reactor with a feed rate of about 100 g h − 1. Pyrolysis at temperatures between 500 and 750°C resulted in the production of gas, liquid and solid fractions with hydrocarbon yields of the organic fraction present in the feed increasing from 60 -85% with increasing pyrolysis temperature. While the hydrocarbon pyrolysis product yield increased with pyrolysis temperature, the yield of the oil fraction was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 14 publications
6
58
0
Order By: Relevance
“… reuse of SR as landfill day cover [50][51][52];  reuse of SR as a hydroponic garden growing medium [53];  use of the organic portion of SR as an alternative fuel source or reducing agent in blast furnaces [50,54,55];  use of SR as an alternative fuel and mineral feedstock for cement production [55,56];  recycling of SR in the manufacture of composite plastic building products, e.g., plastic lumber [57,58];  pyrolysis of SR to produce a synthetic coal/fuel product [51,55,[59][60][61][62]; and  recycling of SR plastics, involving the conversion of the plastics into low molecular weight hydrocarbons (such as via low-temperature, catalytic conversion) for reuse as chemicals or fuels [55,62,63].…”
Section: Alternative 3-pursue Recovery Without Plastics Segregation (mentioning
confidence: 99%
“… reuse of SR as landfill day cover [50][51][52];  reuse of SR as a hydroponic garden growing medium [53];  use of the organic portion of SR as an alternative fuel source or reducing agent in blast furnaces [50,54,55];  use of SR as an alternative fuel and mineral feedstock for cement production [55,56];  recycling of SR in the manufacture of composite plastic building products, e.g., plastic lumber [57,58];  pyrolysis of SR to produce a synthetic coal/fuel product [51,55,[59][60][61][62]; and  recycling of SR plastics, involving the conversion of the plastics into low molecular weight hydrocarbons (such as via low-temperature, catalytic conversion) for reuse as chemicals or fuels [55,62,63].…”
Section: Alternative 3-pursue Recovery Without Plastics Segregation (mentioning
confidence: 99%
“…However, for the development of an industrial scale process, a continuous reactor system would be required to ensure commerciality. Among various reactors for the thermal processing of waste plastics, the continuous screw kiln has been proposed to be a preferred reaction system for industrial commercialization (Aguado et al, 2002, Day et al, 1999, Serrano et al, 2003. Furthermore, it has been suggested that the screw kiln reaction system might reduce the over-cracking of plastics, and generate a comparatively narrow range of products that could be reformed in a second stage to produce hydrogen gas (Czernik and French, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining materials include foam, textiles, carpet, rubber, plastics, paint, wood and glass [3,[5][6][7] and are known collectively as automotive shredder residue (ASR). Commonly, shredder facilities process both ELVs and other feedstock (e.g white goods, light iron) together and the resultant waste stream is terms shredder residue (SR).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also contains metal pieces of varying sizes, which makes this very difficult for an analytical laboratory to process. Other studies have reported some metal levels [5,11,12]; they already show metals such as lead to be present at levels of some concern, and raise the question of whether new de-pollution techniques for ELVs can significantly reduce those levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation